Determination of Vitamin B12 in Milk and Dairy Products by Isotope-Dilution Liquid Chromatography Tandem Mass Spectrometry - Baifen Huang; Jingshun Zhang; Mengli Wang; Zengxuan Cai (Journal of Food Quality)
An isotope-dilution liquid chromatography tandem mass spectrometry method was established for the determination of vitamin B12 in milk and dairy products. The samples were spiked with stable isotope-labeled vitamin B12 and digested by pepsin and amylase. The various forms of cobalamin were transformed to cyanocobalamin by potassium cyanide after they were released from the enzymatically digested samples. Cyanocobalamin was extracted and purified by an immunoaffinity SPE cartridge and then measured in multiple reaction monitoring mode (MRM). The linear correlation coefficient (R2) of this method was greater than 0.999 in the range of 2–100 ng/mL. The detection limit and the quantification limit were 0.5 μg/kg and 1.0 μg/kg, respectively. The spiked recoveries ranged from 92.0% to 99.4% at the three spiked levels with the relative standard deviation (RSD) between 1.89% and 4.51%. The measured results of NIST SRM1849a and NIST SRM1869a by the current method are all within the reference value range. The Z value was 0.8 during participating in the FAPAS proficiency test using the developed method in 2021. The method is simple, rapid, accurate, and sensitive, and it is suitable for the determination of vitamin B12 in different types of milk and dairy products such as whey powder, whole milk powder, pure milk, fermented milk, infant formula, and prescription food for special medical purposes.